OWNERSHIP CONCENTRATION’S MODERATING EFFECT ON DIVIDEND PAYOUT AND TOBIN’S Q OF LISTED CONSUMER GOODS FIRMS IN NIGERIA - Ovbe Simon Akpadaka (Gusau Journal of Accounting and Finance, 2024)
This paper examines the direct effectof ownership concentration (OWNC), dividend policy as proxied by dividend payout (DPAY) and firm size proxied by log of total assets (FS) on firm value which is proxied by Tobin’s Q. Also,the moderating effect of OWNC on the relationship between DPAY and Tobin’s Q was examined. 16 out of the 18 listed consumers goods sector of the Nigerian Exchange Group (NGX)were purposively selected for this study and the study period 2013 to 2022 and 160 statistical observations per variable were employed for the study. Utilizing a ex-post facto research design, and fixed effects regression for the statistical model to control for unobserved heterogeneity withing firms over time, ensuring a robust examination of the relationships under study. Also, an interaction term (OWNC*DPAY) was introduced to capture the joint effects of ownership concentration and dividend policy on Firm value. At the end of the analysis, DPAY was found to have a statistically insignificant impact on firm value. Secondly, OWNC exhibited a significantnegative relationship with firm value, suggesting that higher levels of OWNC could adversely affect firm value. Thirdly, the moderating effect of OWNC on DPAY-firm value relationship yielded a negative and insignificant effect, suggesting that the influence of dividend policy on firm value is not significantly enhanced by variation in ownership concentration. These findings contribute, in a nuanced manner, to literature on dividend policy and ownership concentration in corporate governance in the context of an emerging markets like Nigeria. It is recommended that managers of firms in the sector should look beyond dividend policy for value enhancement strategies and managers should ensure a balancing act between ownership concentration and dispersed ownership because of possible negative impact that concentrated ownership portend.